2015
DOI: 10.2174/1874155x01509010483
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics Analysis of a Gear-Shaft-Bearing System with Breathing Crack and Tooth Wear Faults

Abstract: Considering backlash, time-varying mesh stiffness and radial clearance of bearing, nonlinear dynamic model of gear bearing flexible shaft system is established taking into account breathing crack in shaft and tooth wear. Nonlinear dynamic equations are solved by Runge-Kutta method. Effect of backlash, crack in shaft and tooth wear faults on the nonlinear dynamic behavior of gear-shaft-bearing system is studied. The results show that gear-shaft-bearing system may change from periodic motion to non-periodic moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The fault characteristics were verified through experiments. Cui et al [19] considered tooth backlash, time-varying meshing stiffness, and bearing radial clearance and established a nonlinear dynamic model of a gear-bearing flexible shaft system considering internal breathing cracks and gear tooth wear. The effects of tooth backlash, shaft cracks, and gear tooth wear on the nonlinear dynamic behavior of the gear-bearing system were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The fault characteristics were verified through experiments. Cui et al [19] considered tooth backlash, time-varying meshing stiffness, and bearing radial clearance and established a nonlinear dynamic model of a gear-bearing flexible shaft system considering internal breathing cracks and gear tooth wear. The effects of tooth backlash, shaft cracks, and gear tooth wear on the nonlinear dynamic behavior of the gear-bearing system were studied.…”
Section: Introductionmentioning
confidence: 99%
“…In Darpe (2007) and Al-Shudeifat and Butcher (2011), the flexibility matrix method was utilized for modeling the stiffness of the cracked rotor with breathing crack. Taking breathing crack in shaft and tooth wear into account, Han et al (Cui and Cai, 2015) established a nonlinear dynamic model of gear bearing flexible shaft system. Meantime, the dynamic analysis of a gear system with a breathing slant crack was performed in (Han et al , 2012), and the effects of position, crack depth and type (transverse or slant) on the system dynamic behaviors were considered in the discussion.…”
Section: Introductionmentioning
confidence: 99%
“…10 studied the vibrations of a gear pair with cracks and later analysed the influence of a profile modification on the vibrations of the system. Cui and Cai 11 considered the factor of a shaft crack when studying a gear system. He found that the appearance of a crack fault can increase the chaos motion region and result in instantaneous tooth separation and double-sided impact faults that indirectly intensify tooth wear.…”
Section: Introductionmentioning
confidence: 99%